Analysis of Non-Uniform Flow in Regular Cross-Sectional Channel with Locally varied Resistance Zone: In the Case of Resistance Zone composed of Pile series - Mori, Nozomu; Takahashi, Mikiko; Kinose, Koichi (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 1998)
Flow in regular cross-sectional channel with locally varied resistance zone near the one-sided wall is chosen as the subject of this study. The resistance zone is composed of pile series arranged like vegetation belt or rough stone zone. The lateral distribution of depth-averaged velocity within a cross section is firstly estimated from equation of motion in which we consider the eddy diffusion due to interaction between distributed piles. Secondly longitudinal water level is calculated on the basis of one-dimensional specific energy equation taking account of the lateral velocity distribution due to the pile zone. The comparison of the experimental results with the calculated values supports the availability of the analyses.